Exponential versus linear tapering in junior elite soccer players: effects on physical match performance according to playing positions - Krespi, M.; Sporis, G.; Popovic, S. (Montenegrin Journal of Sports Science and Medicine, 2019)
The purpose of the present study was to investigate the effects of exponential and linear tapering protocols on the distance covered according to playing positions among junior elite soccer players. One-hundred and fifty-eight junior elite soccer players (mean age: 17.07±0.79 years; mean height: 177.85±6.64 cm; mean weight: 71.27±7.96 kg; mean body-mass index: 22.50±1.66 kg/m²) were randomly selected into two groups: (1) exponential and (2) linear tapering group. Training sessions were conducted three times a week for eight weeks. After four and eight weeks of the tapering period, participants were measured in the distance covered according to four basic playing positions on the field: (1) goalkeepers, (2) defenders, (3) midfielders, and (4) forwards. The results showed that the largest effects between the pre- and post-measurement had defenders in the exponential and goalkeepers in the linear group, goalkeepers in the distance covered by slow and medium running in both groups, forwards in fast running and sprinting in the exponential group, and midfielders in the linear group. In conclusion, our results suggest that the exponential tapering protocol brought somewhat larger effects, especially in fast running and sprinting in forwards and slow and medium running in goalkeepers. Future studies need to implement both the exponential and the linear tapering protocols in order to enhance performance but favouring the exponential to produce larger effects.